Keputusan Investasi Melalui Struktur Modal dalam Menentukan Nilai Perusahaan dengan Sub Model Matematika Path Analysis pada Perusahaan Properti Dan Real Estate - Mika Debora Br Barus; Meigia Nidya Sari; Farah Soufika Thahirah (Jurnal Riset Akuntansi dan Bisnis, 2022)
This research aims to prove the influence of investment decisions on the value of companies with capital structures as vaiabel intervening in property and real estate companies listed on the IDX. The data used is the annual report of each company. The analytical method used in this study is the associative method. The sampling method used is purposive sampling with a total sample of 10 Property and Real Estate Companies listed on the IDX and data from 2014 2019. The results of this study indicate that investment decisions partially have no significant effect on the capital structure of Property and Real Companies. Estate listed on the IDX. Investment decisions partially have a significant effect on firm value in Property and Real Estate Companies listed on the IDX. Partial capital structure has no significant effect on firm value in Property and Real Estate Companies listed on the IDX. Investment decisions and capital structure simultaneously have a significant effect on firm value in Property and Real Estate Companies listed on the IDX. Capital structure is not an intervening variable between investment decisions and firm value in Property and Real Estate Companies listed on the IDX